Whichwood - Mafi, Tahereh (Speak, 2018)
Laylee finds herself utterly alone after her mother's death sent her father into a downward spiral of grief. As the last mordeshoor of her village she finds herself lost in the work of preparing the dead for the afterlife. But Laylee's tiresome world is turned upside down when two familiar strangers walk into her life and show her the power of friendship.